Salivary and serum malondialdehyde levels in type 2 diabetes mellitus with dental caries - Hegde, Mithra N; Shetty, Nireeksha; Shetty, Preethesh (International Journal of Dental Research, 2015)
The aim of the study was to evaluate the salivary and serum Malondialdehyde levels in type two diabetes mellitus patients with dental carries. The study was conducted among 80 individual, which included experimental and control group with 40 individuals each divided based on presence and absence of type two diabetes mellitus and DMFT score. The results showed significant increase in salivary and serum Malondialdehyde in type two diabetes mellitus patients with dental caries compared to the control group which comprised of indi-viduals in absence of caries and no diabetes mellitus. Thus, confirming increased oxidative stress in type two diabetes mellitus individuals.